Wnt-pathway inhibitors with selective activity against triple-negative breast cancer: From thienopyrimidine to quinazoline inhibitors - Boudou, Cédric; Mattio, Luce; Koval, Alexey; Soulard, Valentin; Katanaev, Vladimir L. (Frontiers in Pharmacology, 2022)
The Wnt-pathway has a critical role in development and tissue homeostasis and has attracted increased attention to develop anticancer drugs due to its aberrant activation in many cancers. In this study, we identified a novel small molecule series with a thienopyrimidine scaffold acting as a downstream inhibitor of the β-catenin-dependent Wnt-pathway. This novel chemotype was investigated using Wnt-dependent triple-negative breast cancer (TNBC) cell lines. Structure activity relationship (SAR) exploration led to identification of low micromolar compounds such as 5a, 5d, 5e and a novel series with quinazoline scaffold such as 9d. Further investigation showed translation of activity to inhibit cancer survival of HCC1395 and MDA-MB-468 TNBC cell lines without affecting a non-cancerous breast epithelial cell line MCF10a. This anti-proliferative effect was synergistic to docetaxel treatment. Collectively, we identified novel chemotypes acting as a downstream inhibitor of β-catenin-dependent Wnt-pathway that could expand therapeutic options to manage TNBC.